1984
DOI: 10.6028/nbs.tn.1203
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-cost model of residential fire sprinkler systems

Abstract: This paper develops and applies decision models for evaluating the economic efficiency of providing fire loss mitigation in houses through the use of a new technology: fast-response sprinkler systems. A model is developed for calculating present value net benefits as they would accrue to an owneroccupant or an owner of a rental house who installs a sprinkler system. Costs and benefits of owning a system are estimated for selected hypothetical cases pertaining to a new, single-family dwelling in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
0
17
0
Order By: Relevance
“…The benefit-cost analysis in this report is consistent with ASTM E 1074-06: Practice for Measuring Net Benefits for Investments in Buildings and Building Systems, and it is meant to provide a current benefitcost analysis of residential fire sprinkler systems, updating NBS Technical Note 1203: A BenefitCost Model of Residential Fire Sprinkler Systems, published in 1984. In 1984 suggested that sprinkler systems were not cost-effective, perhaps explaining the relatively small number of houses equipped with fire sprinklers today, even while fire professionals maintain that such systems protect lives and property from fire.…”
Section: Executive Summarymentioning
confidence: 85%
See 4 more Smart Citations
“…The benefit-cost analysis in this report is consistent with ASTM E 1074-06: Practice for Measuring Net Benefits for Investments in Buildings and Building Systems, and it is meant to provide a current benefitcost analysis of residential fire sprinkler systems, updating NBS Technical Note 1203: A BenefitCost Model of Residential Fire Sprinkler Systems, published in 1984. In 1984 suggested that sprinkler systems were not cost-effective, perhaps explaining the relatively small number of houses equipped with fire sprinklers today, even while fire professionals maintain that such systems protect lives and property from fire.…”
Section: Executive Summarymentioning
confidence: 85%
“…But, while there is growing recognition of the ability of residential sprinkler systems to protect life and property from fires, less than 1 % of all existing one-and two-family dwellings involved in a structure fire in 2005 had a sprinkler system. Although residential sprinkler systems protect lives and property from fire, earlier research suggested that sprinkler systems were not cost-effective (Ruegg and Fuller 1984;Juas and Mattsson 1994). This might partly explain the dearth of fire sprinkler systems in residential dwellings.…”
Section: Executive Summarymentioning
confidence: 99%
See 3 more Smart Citations